1998
DOI: 10.1161/01.cir.97.19.1897
|View full text |Cite
|
Sign up to set email alerts
|

Real-time Three-dimensional Echocardiography for Determining Right Ventricular Stroke Volume in an Animal Model of Chronic Right Ventricular Volume Overload

Abstract: The real-time 3D system provided good estimation of strictly quantified reference RV stroke volumes, suggesting an important application of this new 3D method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
57
0
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 149 publications
(59 citation statements)
references
References 15 publications
1
57
0
1
Order By: Relevance
“…Three-dimensional imaging techniques may have the potential to provide more accurate information for TV deformation and RV function and geometry. [25][26][27] …”
Section: Study Limitationsmentioning
confidence: 99%
“…Three-dimensional imaging techniques may have the potential to provide more accurate information for TV deformation and RV function and geometry. [25][26][27] …”
Section: Study Limitationsmentioning
confidence: 99%
“…Several recent studies have demonstrated the potential improvements in the evaluation of global LV function from RT3DE data. 10,11 However, analysis procedures applied to 3D data did not fully exploit the volumetric information, because they were still based on tracing of endocardial boundaries on selected planes and on geometric modeling. 12 Because modeling may be inaccurate under certain conditions, the use of information limited to 2 dimensions renders this procedure subject to many of the same limitations as the techniques used to analyze 2DE images.…”
mentioning
confidence: 99%
“…The new functional imaging approach may yield important kinematic information on the distribution of instantaneous velocities in the RV diastolic flow field of specific normal or diseased hearts. cardiac image analysis; ventricular function; cardiac fluid dynamics; right ventricle; heart chamber volume QUANTITATIVE ANALYSIS of three-dimensional (3-D) digital cardiac images has become increasingly important given the recent advances in the digital cardiac imaging techniques of 3-D echocardiography, magnetic resonance imaging, computed tomography, and digital fluoroscopy (1,24,26). The growth of these digital imaging techniques is accompanied by an increasing usage of image manipulation tools, providing more elaborate image analysis and measurement and quantitative evaluation and leading to more refined diagnostic accuracy than visual interpretation alone.…”
mentioning
confidence: 99%